Dampak Bullying terhadap Rasa Percaya Diri Siswa dan Normalisasi Budaya Mental Crab: Studi Kasus Kualitatif di MTsN 1 Lamongan - Fira Putri Salsabella; Ragwan Albaar (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2026)
This study aims to analyze the school’s efforts to foster social empathy and positive character as a preventive strategy against bullying behavior and the formation of crab mentality culture in the school environment. This research employs a qualitative approach with a case study method conducted at MTsN 1 Lamongan, focusing on the 7F class students as research subjects. Data were collected through participatory observation, in-depth interviews, and documentation to explore the experiences of students, counseling teachers, and homeroom teachers in addressing bullying and peer-undermining behaviors. The findings reveal that bullying in class 7F predominantly takes verbal and social forms that are often perceived as harmless jokes but significantly affect students’ self-confidence and learning motivation. The crab mentality culture emerges from the normalization of mockery toward high-achieving students, leading to social fear and hindering the development of positive character. Through group counseling activities, empathy training, and student appreciation programs, the school successfully strengthened social empathy values, fostered mutual respect, and created a more supportive and inclusive learning environment. This study emphasizes the importance of character education in shaping a healthy, empathetic, and bullying-free school culture.